A simple and green photoreduction approach for synthesis of Au/g-C3N4 hybrid nanocomposites with high solar light photocatalytic activity. (1st March 2022) - Linh, Pham Hoai; Chung, Pham Do; Oanh, Le Thi Mai; Van Khien, Nguyen; Bach, Ta Ngoc; Thai, Le Tien; Hang, Lam Thi; Hung, Nguyen Manh; Van Thanh, Dang
Abstract: In this study, we developed a green and easy to scale up approach for producing Au/g-C3 N4 (Au/GCN) hybrid plasmonic photocatalyst without using the chemical reducing agents via the growing of Au nanoparticles (Au NPs) on the surface of GCN nanosheets under the photo-reduction of ultraviolet (UV)-radiation. Different characterization techniques were conducted for investigating the structure, morphology, surface chemistry and optical properties of the as-prepared catalysts. The scanning electron microscope image shows that the homogeneous Au NPs anchored on the surface of the GCN nanosheet increased with the UV illumination time. The x-ray photoelectron spectroscopy results prove the coexistence of GCN nanosheets with heptazine heterocyclic ring (C6N7) units and Au NPs in the Au/GCN. The photoluminescence intensity decreased sharply with the time of UV irradiation, indicating that the recombination rate of photogenerated electron–hole recombination decreased. The photocatalytic activity of the hybrid catalysts was evaluated by degrading rhodamine B (RhB) under simulated sunlight irradiation. The results show that the Au/GCN photocatalyst exhibits superior sunlight photocatalytic activity than that of bare GCN. The 6 h irradiated fabricating sample exhibited the strongest photocatalytic activity, completely decomposing the 10 ppm RhB in 30 min of irradiation. This report can provide the design of a simple and green synthesis method for the highly active Au/GCN photocatalyst.